Pupillary responses to single and sinusoidal light stimuli in diabetic patients - Wolfgang H. Zangemeister; Thilo Gronow; Ulrich Grzyska (MDPI AG, 2009)
We examined effects of diabetes mellitus (DM) on the pupillary light reflex (PLR). Phasic pupillary response to a single light stimulus (200 ms) (pPLR) and to continuous sinusoidal stimuli with four different frequencies (0.1, 0.3, 0.7, 1.3Hz) (cPLR) were examined in 52 DM patients and 21 control subjects. We asked: does recording and frequency analysis of cPLR together with short time fourier [STFT] analysis of pPLR differentiate better between DM patients and normal subjects than pPLR only? Initial pupil diameter was significantly decreased in the DM group. For pPLR. maximal contraction velocity (Vmax), Vmax of redilation 1, reflex-amplitude and pPLR latency were significantly reduced in those patients who also showed signs of diabetic autonomic neuropathy (DNP). Tests of dynamic pupillary light reflex (cPLR) revealed that all DM patients had a significantly reduced gain at lower frequencies. Pupil phase lag was greater at 0.1 and 0.3Hz and smaller at 0.7 and 1.3 Hz in the DNP group (p